ANALISIS PELAKSANAAN PROGRAM KEMITRAAN DAN KINERJA KEUANGAN MITRA BINAAN SEBELUM DAN SESUDAH PROGRAM KEMITRAAN (STUDI PADA MITRA BINAAN PT. TELEKOMUNIKASI INDONESIA, TBK. REGIONAL IV JATENG & DIY) - Ayu Maylani; Wahyu Hidayat (Universitas Diponegoro, 2019)
PT. Telekonumikasi Indonesia, Tbk. is one of the state-owned companies that implement partnership programs. Routine training activities are carried out with material on production management, marketing, online-based training and financial accounting. The success rate of the partnership program is measured through the level of smoothness of the assisted partners in paying installments each month and the financial performance of small businesses with a comparison of financial ratios. The method used in this study is a mixed method. The results showed that based on the triple helix theory, PT. Telkom plays a role as a government in the form of facilitators and regulators on the course of the partnership program. The role of business in supporting partnership programs is to become investors and mentors in training activities. While the role of academics is not visible due to the CDC Unit of PT. Telkom Semarang does not cooperate with any college. The lack of synergy carried out by Telkom caused the effectiveness of the partnership program to be less than optimal. Extensive regional empowerment has made it difficult to coordinate with fostered partners because of the limited resources of CDC staff, long distances, and difficult terrain to reach.